How beliefs and policy characteristics shape the public acceptability of nutritional policies: a survey study in Germany - Andreas, Marike; Kaiser, Anna K.; Dhami, Raenhha; Brugger, Vincent; Sniehotta, Falko F. (Health policy, 2025)
Background - Despite the high prevalence of obesity in Germany, few effective political measures have been implemented to protect population health and improve the sustainability of food systems. One argument frequently raised against policy implementation is the lack of acceptability for policy measures in the German population. - Aim - We aimed to evaluate the acceptability of policy measures currently discussed in Germany's national nutrition strategy and how perceived policy characteristics and participant characteristics influence policy acceptability. - Method - We conducted an online survey with 2001 participants between 06.12.2023 and 05.01.2024, in which we collected data on perceived policy characteristics (acceptability, equity, societal and personal effectiveness), as well as participant values and beliefs. - Results - Most policies were highly acceptable, with policies such as the introduction of free school lunches (84 % acceptability), the introduction of a ban on fast food advertising aimed at children (71 %) or a sugar tax (53 %) being acceptable to a majority of the sample. The least acceptable policy was the introduction of a tax on animal products (36 %). Logistic regression analyses showed that perceived equity and societal and personal effectiveness predicted policy acceptability. Likewise, environmental values and beliefs about state intervention of participants influenced policy acceptability. - Conclusion - The high acceptability observed in this study suggests an opportunity for German policymakers to implement evidence-based and acceptable nutritional strategies to improve population health.